Food loss in international trade in the Asia-Pacific region: Country case study on Bangladesh - Sheikh Morshed Jahan (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2023)
The global food supply chain experiences a loss of approximately one-third of the food produced, making food loss in international trade a significant threat to food and nutrition security and economic loss. Bangladesh, a major producer of vegetables and fruits, faces constraints such as post-harvest management, inadequate transportation and storage facilities, limited access to quality seeds, and stringent quality standards imposed by importing countries. The country also faces non-tariff measures and other obstacles to trade, with the agri-food products sector being the most affected. The lack of cold storage systems and specialized transportation facilities, inadequate port facilities, and weak trade governance are the main causes of food loss in the fruit and vegetable trade. Good agricultural practices, post-harvest management practices, and value chain efficiencies are lacking, resulting in a significant amount of food loss. To mitigate food loss, compliance with good agricultural practices and SPS measures, effective post-harvest practices, and a vapor heat treatment facility, packaging, and cool chain are essential. The government of Bangladesh should also incentivize private sector investment, ease regulatory requirements, and develop a cohesive export-oriented institutional ecosystem to reduce food loss in international trade.
Keywords: F14; Q22; 330; food loss; non-tariff measures (NTMs); border rejections; Asia-Pacific